Synthesis Methods and Crystallization - Marzouki, Riadh (IntechOpen, 2020)
New crystalline materials (organic, inorganic, hybrid) are promising for various applications, including electrical, piezoelectric, ferroelectric, magnetic, and catalytic processes. In addition, given their remarkable structural richness, these materials exhibit several interesting physical properties, such as ionic conduction, ion exchange, and others. Crystal growth, morphology, and grain size are factors influencing these physical properties. This book examines methods of synthesis of the most common crystalline materials and describes nucleation and crystal growth of various materials.